Urbanization and Decentralization: The changing urban-rural linkages and opportunities of decentralization of services - Joachim von Braun (European Regional Science Association (ERSA), 2014)
"Urbanization and Decentralization: The changing urban-rural linkages and opportunities of decentralization of services" Joachim von Braun, Center for Development Research (ZEF) University of Bonn, Germany This paper explores the relations between urbanization and decentralization. Ever stronger linkages between urban and rural areas represent a challenge for sustainable development. Until now, the widespread view in the economic policy and research, categorizing "rural" as more "remote farming areas" and urban as "crowded cities", has led to their separate treatment, missing important sustainability footprints and poverty-reducing inter-linkages between them. The reality is different. In fact, the farming areas (the very rural) and the megacities (the very urban) co-evolve along a continuum with multiple types of flows and interactions. These dynamics are bringing the two spaces ever closer in space and livelihood patterns, leading to the loss of traditional distinctions between them. This gives an important potential role to decentralization of government, and decentralization of services in particular. Decentralization is an instrument for efficient and participatory governance. It has emerged as one of the most important governance reforms in recent history: Approximately 80 percent of all developing and transition countries have implemented this reform in past three decades. Based on a systematic review of country experiences this paper highlights the need for new attention to the spatial dimensions of development and to urban-rural linkages for sustainable development and reviews the evidence of synergies and pitfalls between urbanization and decentralization with concepts of economic geography, and institutional economics. There is evidence that the poorer segments of societies often do not benefit as much from decentralization as the better-off, and in some cases, decentralization even makes matters worse for them. An important reason for this mixed experience is the fact that the impact of decentralization on poverty depends on design- and context-specific factors. Institutional arrangements that work in one situation may not be appropriate for another, which has led to the appeal to move "from best practice to good fit." Against this context, this paper addresses the specific question: how to guide urban-rural linkages toward sustainable development. Strong linkages enhance people's welfare and growth because they facilitate the flow of resources to where they have the largest net economic and social benefits. However, such linkages cannot be taken for granted in development; they must be optimally invested in to help reduce transaction costs related to the linkages of diverse types and stimulate positive externalities and spillover effects. Urban-rural linkages need more policy attention, which requires that adequate institutional and organizational structures be put in place, necessitating appropriate coordination mechanisms between central and local governments.
Keywords: H75; O18; R11; 330